The Impact of Skipping Rope Training on Squat Style Long Jump Outcomes - Hanif Hanif (Joska: Jurnal Isori Kampar, 2024)
Background: The specific effects of skipping rope training on squat style long jump performance are not well-explored, prompting this research to examine the effects of an 8-week program on performance and biomechanics. Methods: Thirty male high school student-athletes were randomly divided into an experimental group receiving skipping rope training and a control group maintaining standard training, with various performance parameters measured pre- and post-intervention. Results: The experimental group exhibited significant improvements in long jump distance and take-off mechanics, along with enhancements in vertical jump height and reactive strength, with multiple regression analysis indicating that reactive strength and coordination were key predictors of performance improvement. Conclusion: The 8-week skipping rope training program significantly improved squat style long jump performance, suggesting its efficacy as a supplementary training method for enhancing explosive power and technical efficiency in athletes.